(n,α) Reaction Cross Sections and Angular Distributions for Several MeV Neutrons - Ts, Zolbadral; Ts, Bilguun; G, Khuukhenkhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this work from the unified viewpoint using the TALYS code we analysed the experimental (n,α) cross sections, angular distributions of 39K and 64Zn, and the ratio of forward/backward cross-sections of 95Mo, 143Nd, 147Sm and 149Sm isotopes at the 4.0-6.5MeV energies of neutrons.